Green textile dyeing process by using natural dyes: a review - Mahmood, Salwa; Nasir, Siti Hana; Sazali, Nurul Aqilah; Wan Yusof, Wan Muhamad Alif (Penerbit UTHM, 2020)
In the textile industry, up to 200,000 tons of dyes are lost to effluents every year during the dyeing and finishing operations, due to the inefficiency of the dyeing process. Today, the textile industry used average six hundred dyes and chemical for the in production of textile dyeing industry (Christy, 2014). Due to the toxicity of dyes and chemicals used in textile dyeing processes has led to both human health and environment directly or indirectly. Therefore, “Go-green” or going green is one alternative way to maintain the sustainability and productivity of textile dyeing industry hence maintaining natural ecological balance in the environment and preserving its natural system and resources. The textile dyeing industry makes a big contribution to the economic growth and has become a massive industry throughout the years. This is because higher demand in the production of synthetic dyes since they are affordable, good colour fastness, has various of colours available and are easy to manufacture. However, the environmental impact arising from these industries aroused attention in today’s society. In terms of pollution, the textile dyeing industries has been condemned as one of the world’s most offensive industry among other sectors in the world. In fact, World Bank stated that textile processing polluted 20% of water pollution globally.